2021
DOI: 10.3906/kim-2009-58
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of enhanced hydrazine electrochemical sensor based on gold nanoparticles decorated on the vanadium oxide, ruthenium oxide nanomaterials, and carbon nanotubes composites

Abstract: This work describes the synthesis of mixed oxide film of vanadium and ruthenium by pulsed deposition technique on multiwall carbon nanotubes and the decoration of gold nanoparticles on the mixed film. A ternary electrocatalyst has been developed for the electrochemical oxidation of hydrazine by combining two metal oxide mixtures with Au nanoparticles. Surface morphology and chemical composition of the electrode have been examined with SEM, EDX, HRTEM, EIS, and XRD. The peak current of hydrazine increased 9 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Karaca et al 193 reported the nanoscale dimension of AuNPs/(VO x −RuO x )/CNT/GCE fabricated via the EC method. Both the amperometric and LSV methods for N 2 H 4 produce a WLR of 2.5−10000 μM and concentration range 0.03−100 μM and an LOD of ∼0.5 μM and 0.1 μM at S/N = 3 by voltammetric techniques.…”
Section: •−mentioning
confidence: 99%
“…Karaca et al 193 reported the nanoscale dimension of AuNPs/(VO x −RuO x )/CNT/GCE fabricated via the EC method. Both the amperometric and LSV methods for N 2 H 4 produce a WLR of 2.5−10000 μM and concentration range 0.03−100 μM and an LOD of ∼0.5 μM and 0.1 μM at S/N = 3 by voltammetric techniques.…”
Section: •−mentioning
confidence: 99%